2022
DOI: 10.2991/assehr.k.220301.139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Risk Management on Firm Performance

Abstract: The aim of this paper is to investigate whether the relationship between risk management and firm performance. Risk disclosure and leverage are the measurements of risk management. Tobin's Q is proxy for firm performance. This study use panel data from 36 listed companies during 11 years from the period 2007 to 2017 with 396 observations. The result from the STATA program is shown that risk disclosure has significant impact on Tobin's Q. Leverage has a Positive correlation on Tobin's Q. Both the variables of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In contrast, some studies claimed that more reported negative risk disclosures in the firm annual reports will affect its financial performance severely [1,9,87].…”
Section: Risk Disclosure Quality Cost Of Equity and Firm Performancementioning
confidence: 97%
“…In contrast, some studies claimed that more reported negative risk disclosures in the firm annual reports will affect its financial performance severely [1,9,87].…”
Section: Risk Disclosure Quality Cost Of Equity and Firm Performancementioning
confidence: 97%
“…Risk management is an essential topic for the business. Risk management is an indication of a company's openness, which will influence investors' decisions and improve business performance (Azizah, 2022). Good company value is one of the factors considered by investors, including those in the financial industry, when deciding to invest in a company.…”
Section: Risk Managementmentioning
confidence: 99%